(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
As a registered tourist guide, you’ll need to have the right qualifications and training, abide by the code of conduct, and have first aid training. The safety of our visitors is important to us. Travelling with a registered tourist guide will ensure their well-being and give them the best experience possible